Rapid Exhumation Processes of the Gaoligong Mountain Range in the Southeastern Margin of the Qinghai–Tibet Plateau Since the Late Cenozoic - Wang, Jialong; Li, Ni; Stuart, F. M.; Nicola, L. D.; Zhang, Huiping; Wang, Ying; Pang, Jianzhang; Zhao, Yongwei (Frontiers in Earth Science, 2022)
Three continent-scale ductile shear zones trending N-S are distributed in the southeast margin of the Qinghai–Tibet Plateau. Their tectonic deformation and exhumation histories are of great significance to understanding the orogenic processes within the continent and the growth as well as expansion mechanism of the plateau. The Gaoligong shear zone (GLGSZ) is the westernmost zone near the boundary of the Indian subduction plate and is less well studied than the Ailaoshan–Red River shear zone (ASRRSZ) in the east. In this study, low-temperature thermochronological methods including apatite (U-Th)/He (AHe), zircon (U-Th)/He (ZHe), and apatite fission track (AFT) were used to date the vertical profile samples from the Gaoligong Mountain to understand the exhumation processes that occurred in the late Cenozoic. Our results show that the GLGSZ has experienced two stages of rapid exhumation events since the late Cenozoic: in the middle Miocene (~14.5 Ma) and early Pleistocene (~2.9 Ma). Based on our data, we divided the late Cenozoic tectonic deformation and exhumation processes in the Gaoligong Mountain area into two stages: 1) From the middle to the late Miocene, large-scale regional dextral strike-slip movements and lateral compressions controlled the ductile shear zone and continuously denuded the mountain surface; 2) in the Pleistocene, rapid river erosion and undercutting caused by fluctuations of the monsoon system, together with the continuous activity of brittle faults, drove the latest rapid exhumations. A comparison of the thermochronological data of the different areas along the Gaoligong Mountain shows that the exhumation rate in its northern transect is significantly higher and the time of the onset of exhumation is earlier than that in the southern transect. These results indicate that the deformation processes began in the north and continued southwards and controlled the geomorphological characteristics of the Gaoligong Mountain, whose elevation is higher in the northern part than in the southern part.